ANALYSIS OF THE EFFECTIVENESS AND EFFICIENCY OF THE REGIONAL BUDGET REALIZATION IN BANTEN PROVINCE FOR 2020–2024: A REGIONAL FISCAL BALANCE PERSPECTIVE - Septi Nurmalita; Rochma Sudiati; Deas Shaqilla Putri (STIESA Press, 2025)
This study analyzes the effectiveness and efficiency of the realization of the Regional Revenue and Expenditure Budget (APBD) of Banten Province for the years 2020–2024 and its implications for the region's fiscal balance. Using a descriptive qualitative approach and ratio analysis, the study evaluates the performance of revenue realization, expenditure efficiency, and trends in fiscal balance. The results indicate that regional revenue realization generally falls into the effective to highly effective category, reflecting strong fiscal capacity. However, expenditure efficiency shows fluctuations, with two years classified as efficient and the remaining three years as less efficient or inefficient, indicating the need to strengthen budget discipline. In terms of fiscal balance, Banten Province experienced a surplus in 2020 and 2024, while in 2021–2023, a deficit occurred, though still within moderate limits. These findings highlight the importance of improving fiscal management and budget planning to maintain regional fiscal stability sustainably. This research provides empirical contributions to local governments in enhancing APBD performance and strengthening long-term fiscal independence.